Syntactic Analysis of Makassar Question Words: An X-Bar Theory Approach - Rahmah, Aisyah Tiara; Subiyanto, Agus (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2024)
This article endeavors to scrutinize the creation and functionalities of interrogative constructions, with a specific emphasis on the Makassar Language. The research design employed in this study involved the use of primary sources and followed a descriptive approach. Data collection was carried out through conversations with Makassar participants. To analyze the syntactic data, the study adopted X-Bar Theory as its theoretical foundation, which was then depicted in the form of syntax trees. The findings of this study indicated that the Makassar Language serves two grammatical functions, namely as a specifier and a complement. The highest level of projection in this structure was the Complementizer Phrase/CP. The distinction between these functions lay in the placement of question words. When a question word was positioned at the beginning of a sentence, it functioned as a specifier and followed the interrogative structure rule of QW + Subject + Predicate + Adv (optional). On the other hand, question words that required an answer other than the subject or were positioned at the end of a sentence were referred to as complementary functions. In this function, the researcher identified the pattern where the structure was written as Subject + Predicate + QW. X-Bar theory also helps in teaching syntax which needs a lot practice including creating tree diagrams of sentences to parse each constituent that requires a platform or program that can lead the students to diagramming